Pengaruh Edukasi Video Animasi terhadap Keterampilan Ibu dalam Melakukan Tekhnik Pijat Tui Na pada Bayi dan Balita - Juwita, Juwita; Suriana, Suriana (Jurnal Midwifery, 2026)
Background: Infancy and the toddler years constitute a crucial early period in a child's life, making them vulnerable to growth and developmental issues. Infancy spans the ages of 0–12 months, while the toddler stage covers ages 1–5 years. Common issues encountered during these stages include nutritional needs and malnutrition (specifically stunting). Education using animated video media is an effective method for improving mothers' skills in performing Tui Na massage techniques. Objective: This study aimed to determine the effect of animated video-based education on improving mothers' skills in performing Tui Na massage techniques on infants and toddlers. Research Methods: This was a quantitative study utilizing a one-group pretest-posttest design. The sample consisted of mothers with infants and toddlers who met the inclusion criteria. The instrument used was a questionnaire assessing technique skills, administered before and after the intervention; data were analyzed using the Wilcoxon statistical test. Results: Analysis revealed an improvement in skills following education via animated videos on Tui Na massage techniques. Statistical testing showed a significance value of 0.000 (p < 0.05), leading to the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (Ha). Conclusion: It can be concluded that animated video-based education has an effect on improving mothers' skills in performing Tui Na massage techniques on infants and toddlers.